2021
DOI: 10.3389/fgwh.2021.723620
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Adolescent Girls and Young Women on Optimizing Youth-Friendly HIV and Sexual and Reproductive Health Care in Zambia

Abstract: Youth-friendly health care delivery models are needed to address the complex health care needs of adolescent girls and young women (AGYW). The aim of this study is to explore the lived experiences of AGYW seeking comprehensive HIV and sexual and reproductive health (SRH) care and to elicit their preferences for integrated health care services. We conducted in-depth interviews and focus group discussions in Lusaka, Zambia among 69 AGYW aged 10-20 who were HIV-negative or of unknown status and 40 AGYW aged 16-24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The manifestations of AGYW stigma in the clinic described by the health workers in this study also echo the literature on the adolescent perspective, as adolescents have noted excessive questioning and scolding in health facilities as barriers to accessing care [ 10 , 31 ]. Recent literature that explored youth-friendly clinic attributes of importance to Zambian AGYW also found that assurances of confidentiality and provider friendliness were key adolescent expectations when attending the clinic [ 32 ]. In addition, health workers’ comments about shared waiting rooms contributing to confidentiality concerns build on past acknowledgement of the role of the physical layout of the clinic facility as something that can contribute to or mitigate the experience of stigma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of AGYW stigma in the clinic described by the health workers in this study also echo the literature on the adolescent perspective, as adolescents have noted excessive questioning and scolding in health facilities as barriers to accessing care [ 10 , 31 ]. Recent literature that explored youth-friendly clinic attributes of importance to Zambian AGYW also found that assurances of confidentiality and provider friendliness were key adolescent expectations when attending the clinic [ 32 ]. In addition, health workers’ comments about shared waiting rooms contributing to confidentiality concerns build on past acknowledgement of the role of the physical layout of the clinic facility as something that can contribute to or mitigate the experience of stigma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a three-step process to develop a tailored conceptual framework focused specifically on the integrated delivery of care to adolescents within HIV care programs. First, we identified key themes on barriers and preferences related to health care service delivery from prior work done by this team to inform this conceptual framework [ 11 ]. We had previously conducted interviews and focus groups with 109 AGYW aged 10 to 24 years in Zambia as part of formative research conducted for planning an implementation science trial [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…We developed detailed guides and conducted systematic qualitative analysis to identify emergent themes. These details are included in a recently published manuscript [ 11 ]. Second, we created an initial framework that was presented to implementation scientists and researchers attending the Joint Adolescent HIV Prevention and Treatment Implementation Science Alliance (AHISA) and Prevention and Treatment through a Comprehensive Care Continuum for HIV-affected Adolescents in Resource Constrained Settings (PATC 3 H) meeting in February 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations